Correction: Ultrathin titanium oxide nanosheets film with memory bactericidal activity. Issue 44 (28th October 2016) - Wang, Gen; Xing, Zheng; Zeng, Xiangkang; Feng, Chuanping; McCarthy, David T.; Deletic, Ana; Zhang, Xiwang
Abstract : Correction for 'Ultrathin titanium oxide nanosheets film with memory bactericidal activity' by Gen Wang, et al., Nanoscale, 2016, DOI: 10.1039/c6nr06313f.